Nanoparticles effect on magnetic and transport properties of (La₀,₇Sr₀,₃)₀,₉Mn₁.₁O₃ manganites - Dyakonov, V.; Slawska-Waniewska, A.; Kazmierczak, J.; Zubov, E.; Myronova, S.; Pashchenko, V.; Pashchenko, A.; Shemjakov, A.; Varyukhin, V.; Prilipko, S.; Mikhaylov, V.; Piotrowski, K.; et al. (Физика низких температур, 2009)
We report on the magnetic and transport thermal measurements of nanosize (La₀,₇Sr₀,₃)₀,₉Mn₁.₁O₃ manganite. The nanoparticles were synthesized with use of co-precipitation method at different (800, 900 and 950 °C) temperatures. Their crystal structure was determined to be perovskite-like with a rhombohedral distortion (the space group R3̅c). The phase composition and specific surface nanopowders were determined. The average size of synthesized nanoparticles (from 40 to 100 nm) was estimated by both the method of low-temperature adsorption of argon and x-ray diffraction measurements. All the nanosize samples show ferromagnetic-like ordering with close phase transition temperatures. Their magnetization decreases with reducing the particle size. Comparison of experimental and calculated temperature dependences of the spontaneous magnetic moment shows that the spontaneous magnetization both in magnetic field and without field is well described in the frame of the double exchange model. The decrease of magnetization with decreasing particle size is due to increasing the surface contribution to magnetization. The magnetic entropy was shown to increase with increasing applied magnetic field and to be smaller for the small particles. The resistivity was established to become higher with reducing the particles size at any temperatures.